Fungi on the skin of anurans from Coatan river watershed, Chiapas, Mexico - Mejía-Velázquez, Leidy Yadira; Tovar-Juárez, Edgar; Ramos-Pérez, Dory Gledis; Albores-Flores, Víctor; Estrada-Santos, Yaneth; Teco-Bravo, Jalsen Iván (Ecosistemas y Recursos Agropecuarios, 2022)
As a result of the land use change, amphibian populations have been threatened by a species of pathogenic fungus, but there are other species of potentially mortal fungi about which little is know The watersheds of Chiapas coast have been severely altered, and several species of anurans are exposed to pathogenic fungi, therefore the aim of this work was determine the richness fungal species on the skin of anurans from the Coatan river watershed in Chiapas, Mexico. A total of 90 individuals of different species of anurans were collected from lower, middle and upper zones of the watershed. Skin fragments from dorsum and belly of each individual were dissected and cultured in PDA y TGhL medium, isolated and identified to species level when it was possible. Differences between composition of fungi species and environmental variables of each watershed zones were analyzed. A total of 24 fungi species were identified in seven anuran species from different habitat; in the Lower zone, the highest fungi species richness, the highest species number per host and higher species number in the ventral tissue were found. The species composition was different at the middle zone, and all zones were environmentally different. Some fungi genera found here have been reported as pathogens of amphibians, reptiles or plants, no sick or death individuals were observed. Agriculture activities promote the presence of fungi on anurans skin, an these can be natural disperses of pathogenic fungi for several species including those of agricultural importance.